Characterization of lesions in the stomach: Will confocal laser endomicroscopy replace the pathologist?. Issue 4 (August 2015) - Goetz, Martin
Abstract Confocal laser endomicroscopy (CLE) permits microscopic visualization of the mucosa during endoscopy at an approximately 1000fold magnification, permitting endoscopists to obtain microscopic analysis during gastroscopy. This can result in optimized diagnosis of diffuse alterations such as gastric atrophy and intestinal metaplasia and may limit the sampling error of untargeted biopsies. It also allows risk stratification prior to endoscopic therapy of neoplastic lesions of the stomach. In these areas, CLE represents a valuable adjunct for targeted histopathology. In addition, CLE allows on-site in vivo imaging, and by this insight into physiologic and pathophysiologic as well as molecular events of the stomach without major artifacts.